The effect of adding curcumin to sodium valproate in treatment of patients with bipolar disorder in the acute phase of mania: A randomized double-blind clinical trial - Akbarzadeh, Farzad; Niksun, Nabahat; Behravan, Ghazal; Behdani, Fatemeh; Mohammadpour, Amir Hooshang; Jaafari, Mahmoudreza; Hosseini, Tayebeh; Rajai, Zahra; Ebrahimi, Alireza; Eslamzadeh, Mahboubeh (Frontiers in Psychiatry, 2023)
Background: Inflammatory processes play a role in the etiopathogenesis of bipolar disorder type 1. Full therapeutic responses are seldom seen and the ongoing inflammatory processes in the brain could lead to neuronal loss. Curcumin, a relatively safe herbal compound, has been shown to have anti-inflammatory effects. The present randomized double-blind clinical trial study aimed to investigate the effect of adding curcumin to the treatment regimen of BID. Methods: This randomized double-blind clinical trial was conducted on 78 patients diagnosed with BID according to the Diagnostic and Statistical Manual of Mental Disorders (DSM 5) criteria. The sample were divided into two groups. Patients in both groups received sodium valproate starting at a dose of 600 milligrams per day and administered up to 20 milligrams per kilogram per day or the highest dosage of the patient’s tolerance. Patients in the intervention group also received curcumin as nanomicelle in soft gelatin capsules 40 milligrams per day. The control group received placebo tablets with the same characteristics as the curcumin tablets. They were assessed by a psychiatrist using the Young Mania Rating Scale (YMRS), Mini-Mental State Examination (MMSE), Clinical Global Impression (CGI), and a medication side effect questionnaire at the beginning of the study, as well as in the first, second, and fourth weeks of the study. Results: Among the 78 patients chosen to participate in the project, 54 people completed the trial. No specific side effect was observed in the two groups. Both groups showed an increase in their MMSE scores compared to the beginning of the study (p-value<0.001). Although this increase was not statistically different between the two groups (p-value=0.68). The YMRS score of both groups decreased significantly by the end of the study (p-value<0.001); however, this decrease was not significantly different between the two groups (p-value=0.64). In addition, the two groups experienced a significant increase in their CGI scores throughout the study (p-value<0.001), this increase however was not statistically different between the two groups (p-value=0.88). Conclusion: The present study suggested that curcumin may not be a useful adjuvant agent in the management of patients with BID receiving sodium valproate as treatment.